Relationship between Authoritarian Parents and Student Emotions and Implications for Guidance and Counseling - Ultravio Ultravio; Zikra Zikra (Jurnal Neo Konseling, 2021)
Authoritarian parenting is a pattern of parenting in which rules and limits must be obeyed without giving the child the opportunity to state that if the child does not comply, they are threatened and placed. This authoritarian parenting can lead to misunderstandings in children, less initiative and activities, so that the child is not confident in his abilities. Meanwhile, emotion is a response to a stimulant that causes physiological changes accompanied by strong feelings and usually contains the possibility to erupt. This study aims to reveal the relationship between authoritarian parenting and student emotions at SMPN 12 Padang. This research is a descriptive correlational study, with a sample size of 229 students who were obtained using stratified random sampling technique. Stratified random sampling. The data collection instrument used a linkert scale questionnaire which was compiled by itself in data collection using the google forms application. The results of this study are (1) authoritarian parenting styles are generally in the high category with a frequency of 137 and a percentage of 59.8%, these results reveal that authoritarian parenting of students at SMP Negeri 2 Padang is in the high category. This means that many students feel authoritarian parenting style; (2) students' emotions are in the high category with 161 frequency and 70.3% percentage, these results reveal that the emotions of students at SMP N 12 Padang are in the high category. This means that many students are able to recognize their emotions; (3) there is a significant positive relationship between authoritarian parenting and student emotions at SMP Negeri 12 Padang. So, the higher the authoritarian parenting, the higher the students 'emotions, and conversely, the lower the authoritarian parenting, the lower the students' emotions.